APPLICATION OF TECHNIQUE OF VES-STIMULATED PHASAL POLARIZATION FOR PETROLEUM PRODUCTS POLLUTION ESTIMATION OF UPPER PART OF SEDIMENTARY COVER (FOR EXAMPLE OF "USYN" AREA) - VYZHVA, S.; NURMUKHAMEDOV, V.; KACHAN, I.; REVA, M.; NIKITASH, O.; HONCHARUK, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
As a result of parametric investigation with VES-SPP (stimuled phasal polariration) carried out nearby river Uzyn was uncovered that kerosene pollution discreases resistability and increases the polariration of upper part of geological enviromental. So, as a leading method for petroleum products pollution investigations recommend the hindorless technique VES-stimulated phasal polariration with parametric drilling, seismic procpecting and gaz survey.